Flow and Pressure Drop Characteristics of Equal Section Divergent-Convergent Microchannels. (2016) - Singhal, Rohit; Ansari, Mohd. Zahid
Abstract: In this work, a generalized design of non-uniform tapered microchannel is purposed which is correlating different types of nonuniform microchannel. A parameter of purposed channel is used to define three different cases of nonuniform channel. Pressure drop is found by numerical investigation of fluid flow in channel which is carried out in laminar flow conditions. Water is used as working fluid at low mass flow conditions. Three different cases of converging, diverging and equally converging and diverging channel are investigated. Pressure drop in channel is linear dependent on mass flow rate and shows a lower pressure drop in case of equal converging diverging channel. On basis of the study, characteristic length scale is analyzed which can be used to evaluate pressure drop in tapered channel by uniform channel correlation. Characteristic length scale shows a dependency with respect to given three cases. This work established a new concept of generalizing converging diverging passage which can be used further for analysis of channel properties.